2012
DOI: 10.1051/0004-6361/201219656
|View full text |Cite
|
Sign up to set email alerts
|

4U 1626–67 as seen bySuzakubefore and after the 2008 torque reversal

Abstract: Aims. The accretion-powered pulsar 4U 1626-67 experienced a new torque reversal at the beginning of 2008, after about 18 years of steadily spinning down. The main goal of the present work is to study this recent torque reversal that occurred in February 2008. Methods. We present a spectral analysis of this source using two pointed observations performed by Suzaku in March 2006 and in September 2010. Results. We confirm with Suzaku the presence of a strong emission-line complex centered on 1 keV, with the stron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 39 publications
5
35
1
Order By: Relevance
“…A broad Fe Kα emission line is also detected at ∼6.76 keV with a σ of ∼150 eV in both the observations. These line centroid energies and widths are consistent with the results in previous papers (Camero-Arranz et al 2012, Suzaku data; D17, NuSTAR data). We also tried different phenomenological continuum models, the Fermi-Dirac CutOff (FDCO) model (Tanaka 1986) and a power-law modified with a high-energy cut-off (HIGHECUT) model Table 1).…”
Section: Continuumsupporting
confidence: 91%
See 1 more Smart Citation
“…A broad Fe Kα emission line is also detected at ∼6.76 keV with a σ of ∼150 eV in both the observations. These line centroid energies and widths are consistent with the results in previous papers (Camero-Arranz et al 2012, Suzaku data; D17, NuSTAR data). We also tried different phenomenological continuum models, the Fermi-Dirac CutOff (FDCO) model (Tanaka 1986) and a power-law modified with a high-energy cut-off (HIGHECUT) model Table 1).…”
Section: Continuumsupporting
confidence: 91%
“…The pulsar has undergone two torque reversals in recorded history, in 1990 (Chakrabarty et al 1997(Camero-Arranz et al 2010, and is currently spinning up. Suzaku observations bracketing the torque reversal found no changes in the CRSF parameters, despite a factor of ∼2.8 increase in X-ray flux and large changes in the soft X-ray spectrum (Camero-Arranz et al 2012). However, a pulse-phaseresolved study of the 2006 Suzaku observation (during the spin-down state) by Iwakiri et al (2012) reported the possible detection of an emission-line-like feature at the CRSF energy in the dim phase of the pulse profile.…”
Section: Introductionmentioning
confidence: 96%
“…The X-ray broadband (0.5-50 keV) spectral properties, i.e., the hard spectrum ( 1 G~) at lower energies with a cutoff around 15-20 keV, are more consistent with Galactic X-ray pulsars (e.g., Hung et al 2010;Camero-Arranz et al 2012;Fürst et al 2013) than with BH binaries and neutron star binaries with weak magnetic fields (Z-sources and atoll sources). Our observations suggest that there is a soft X-ray excess in this system, and the soft excess has also been seen in several accreting pulsars (e.g., Nagase 2002; Hickox et al 2004).…”
Section: Discussionmentioning
confidence: 84%
“…Jain et al 2010;Camero-Arranz et al 2012). According to Camero-Arranz et al (2012), the spectra in both phases can be fitted with a model composed of a blackbody and a cutoff power law, and their difference is in the blackbody component, whose temperature is ∼ 0.5 keV in the spin-up phase and ∼ 0.2 keV in the spin-down phase. We hence employed these respective spectral models for the spin-up and spin-down phases, and converted the 2-20 keV MAXI/GSC flux to those in the 0.5-100 keV band, which we identify with F bol .…”
Section: Estimation Of Bolometric Fluxmentioning
confidence: 99%